Pengaruh Model Pembelajaran Problem Based Learning (PBL) terhadap Hasil Belajar Materi Fotosintesis Kelas IV Sekolah Dasar - Wahyu Novitasari Karnoto Putri; Iqnatia Alfiansyah; Nataria Wahyuning Subayani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe the influence of the Problem Based Learning (PBL) learning model on the learning outcomes of photosynthesis materials in grade IV elementary schools. The method used in this study is an experimental method with a quasi-experimental type. The design in the study is a non-equivalent control group design. The design of this study involves two classes, the experimental class, namely IV-B, is learning using the Problem Based Learning (PBL) learning model and the control class, namely class IV-C, is learning using the conventional learning model. The sample used was 54 students in grades IV-B and IV-C SD YPI Darussalam. The data collection technique uses a learning outcome test. Based on the results of the study in the Independent Sample T-test which showed a Sig. (2-tailed) value of 0.000 ≤ 0.05 which means less than 0.05, then H0 and Ha were accepted, which means that there is an influence of the Problem Based Learning (PBL) learning model on the learning outcomes of photosynthesis materials in grade IV elementary school.